Evaluasi Desain Lengkung Horizontal Jalan Raya Pada Kawasan Wisata Alam Arak-Arak Kabupaten Bondowoso Jawa Timur - Nain Dhaniarti Raharjo (Institut Teknologi Adhi Tama Surabaya, 2022)
The road is one of the transportation infrastructures that have a role as a connector between regions, and also contributes to the strengthening and growth of the economy, society, tourism, and culture of a region. Today, tourism activity in Indonesia is growing rapidly, marked by the increasing number of tourist areas being built, one of which is the Arak-Arak natural tourism area in the Bondowoso Regency, East Java. Located in a hilly area with an altitude of 345 meters above sea level, with hilly terrain characteristics. Horizontal curvature analysis uses the 2021 Road Geometric Guidelines, assuming a curve model with the S-C-S type. After analyzing according to the planning provisions, the ideal value for the Ls length (Transitional Curve) is 60 meters, the Lc value is 39.215 meters and the ideal total length (Lt) is 159.215 meters. This shows that the condition of the existing horizontal curve has a bend length that is less than ideal when compared to the results of the analysis, namely a shortage of about 70.715 meters and a widening of the bend side of 1.104 meters is also required.